Proximal hypospadias: A persistent challenge. Single institution outcome analysis of three surgical techniques over a 10-year period. Issue 1 (February 2016) - Pippi Salle, J.L.; Sayed, S.; Salle, A.; Bagli, D.; Farhat, W.; Koyle, M.; Lorenzo, A.J.
Summary: Introduction: The optimal treatment of proximal hypospadias remains controversial. Several techniques have been described, but the best approach remains unsettled. Objective: To evaluate and compare the complication rates of proximal hypospadias with and without ventral curvature (VC), according to three different surgical techniques: tubularized incised plate (TIP) uretroplasty, dorsal inlay graft TIP (DIG), and staged preputial repair (SR). It was hypothesized that SR performs better than TIP and DIG for proximal hypospadias. Methods: Single-center, retrospective chart review of all patients with primary proximal hypospadias reconstructed between 2003 and 2013. The DIG was selectively employed in cases with narrow urethral plate (UP) and deficient spongiosum. Extensive urethral plate (UP) mobilization (UPM), dorsal plication (DP) and/or deep transverse incisions of tunica albuginea (DTITA) were selectively performed when attempting to spare transecting the UP. Division of UP and SR was favored in cases with severe VC (>50°), which was often concurrently managed with DTITA if intrinsic curvature was present. For SR, tubularization of the graft was performed 6 months later. Results: A total of 140 patients were included. Tubularized incised plate (TIP), DIG, and SR techniques were performed in 57, 23, and 60 patients, respectively. The TIP and DIG techniques achieved similar success rates, although DIG was performed in cases of narrow and spongiosum-deficient plates. Reoperation rates with TIP and DIG techniques was 52.6% and 52.1% (NS). Urethro-cutaneous fistulas were seen in 31.5% and 13% of TIP and DIG techniques, respectively. Staged repair accomplished better results than both TIP and DIG techniques, despite being performed in the most unfavorable cases (reoperation rate 28%). After technical modifications, the DIG technique achieved similar outcomes of SR. Conclusions: Proximal hypospadias remains challenging, regardless of the technique utilized for its repair. Urethro-cutaneous fistulas were more commonly seen after long TIP repairs. Approximately half of the patients undergoing long TIP and DIG procedures needed re-intervention, although the percentage decreased significantly with late modifications in the DIG group. Recurrence of VC after TIP and DIG techniques seemed to be a significant and under-reported complication. Staged repairs, despite being performed for the most severe cases, resulted in overall better outcomes.